COVID-19 VACCINATION HESITANCY IN SERBIA - Jeremić Stojković, Vida; Cvjetković, Smiljana; Bjegović-Mikanović, Vesna; Gazibara, Tatjana; Sarajlija, Adrijan (Medical Research, 2024)
Introduction/Aim: Vaccine hesitancy is recognized as important determinant of routine immunization coverage, but also as factor of inadequate acceptance of the COVID-19 vaccine. The World Health Organization proposed a “3C” model, with confidence, complacency and convenience as the core components of vaccine hesitancy. The purpose of this study was to assess the intention to receive COVID-19 vaccine through the 3C framework in Serbia.Materials and Methods: This cross-sectional study was based on data from 1,435 adult respondents from general population using an online questionnaire. Convenience, non-probability sampling was applied. Participants were reached through the existing social networks and mailing lists. The main outcome variable was the intention to get vaccinated against COVID-19, with three categories: vaccine refusal, vaccine indecisiveness, and vaccine acceptance. To explore associations of predictor variables (socio-demographics, source credibility, general vaccine attitudes and COVID-19 vaccine hesitancy measured through three scales – Confidence, Convenience and Complacency) with the outcome variable, binary logistic regression models were conducted.Results: Less than one third of respondents (28.6%) were vaccine refusing, 33.7% were vaccine accepting, while 37.7% were undecided. Increased likelihood of being both vaccine undecided and vaccine refusing was significantly associated with lower scores on Confidence and Convenience scales, and a higher score on the Complacency scale.Conclusion: Confidence in health authorities and government, confidence in COVID-19 vaccine safety and efficacy, perception of ease of access to vaccination and complacency (perceived lack of need for vaccination) were the most important factors driving the intention to get vaccinated, confirming relevance of the “3C” model.